New Self-Care Scale for Adults (SCS-A): Development and validation in Spanish parents and its relationship with psychological and family adjustment - Olga Gómez-Ortiz; Carmen Sánchez-Sánchez; Oscar F. Garcia (BMC Psychology)
Abstract Purpose Although there are different instruments that evaluate self-care, most of them have not been validated for use in the Spanish population or in the general adult population. Moreover, there is little evidence on its relationship with psychological and family adjustment. Therefore, the aims of this study were to: (1) validate the self-care scale for adults and (2) analyse its external validity, verifying its relationship with general psychological and family adjustment variables. Methods The sample was constituted by 971 parents (56.5% women) with children in early childhood (0–5 years) aged 23–58 years (M = 38.11). Exploratory and confirmatory factor analyses, correlations and Student’s t mean contrasts were carried out. Results Good fit indices for the scale, which presented a bifactor structure composed of physical and psychological self-care. Both types of self-care were directly related to life satisfaction and positive affect; on the other hand, they were negatively related to parental stress, the presence of family-work conflict, and the guilt related to such conflict. The mothers reflected lower levels of psychological self-care. Conclusions The developed questionnaire is a valid instrument that can be useful in the measurement of self-care in adults and particularly in parents of young children. It is highlighted the need to design initiatives that improve parental well-being through the study construct.